The role of legal autopsy in the investigation of death cases due to medical malpractice [Ölümle sonuçlanan tibbi uygulama hatalarina yaklaşimda adli otopsinin rolü] - (:unkn) unknown (Turkiye Klinikleri, 2008)
Objective: Technological and scientific developments resulted in significant improvements in medical practice; however, medical malpractice claims increased as well in recent years. Material and Methods: Cases of death referred to the Council of Forensic Medicine with the claim of medical malpractice are included in this study. Results: The number of related medical malpractice cases investigated in the 1st and 3rd Boards of the Council between the years 2001-2005 was 525. Of these, 303 were males and 215 were females and in 7 cases the gender was not identified. Considering the responsible clinical units, the majority of the cases were from the emergency unit (28%). Taking the duration of hospitalization into account, the largest group was the group hospitalized for 0-24 hours (51.6%). The ultimate decision was medical malpractice in 92% of the cases, whereas 43 cases (8%) remained inconclusive for various reasons. Concordance between clinical diagnosis and autopsy findings was investigated in order to evaluate the impact of autopsy in the investigation of medical malpractice cases. The most common conditions that resulted with misdiagnosis were aortic aneurysm rupture, myocardial infarct, and pneumonia. Considering the relationship between medical malpractice adjudication and major discrepancies determined at autopsy, conclusion of medical malpractice was significantly higher in the group showing major discrepancies. Conclusion: In conclusion, autopsy is an effective tool in the investigation of cases with the claim of medical malpractice. Copyright © 2008 by Türkiye Klinikleri.
Keywords: Autopsy; Forensic medicine; Malpractice